Does Changing Your Job Leave You Better Off? A Study of Labour Mobility in Australia 2002 to 2008 - Watson, I (National Centre for Vocational Education Research, 2011)
What is the extent of labour mobility in Australia? Why do workers change jobs? How far do workers move when they change jobs? What are the characteristics of those workers who do change jobs and how do they differ from those who don’t? Finally, are workers better off aer changing their job? ese are the core questions which this report addresses.
National Centre for Vocational Education Research Occasional Papers
Keywords: Employment -- Labour mobility; Employment; Labour market; Employment; Labour mobility; Employment and unemployment